Consumer satisfaction and return patronage in specialty coffeehouse in Malaysia - Teh, Chean Boon (2002)
Specialty coffeehouse was a fast growing industry ever since it was introduced to Malaysia in early 1996. Among the established specialty coffeehouse were Coffee Bean & Tea Leaf, Starbucks Coffee and Gloria Jean's Coffee. If the local coffeehouse and restaurant would like to be as competitive as the franchise specialty coffeehouse, it is paramount important to understand the consumers' expectations and needs. Nevertheless, there is lack of theoretical understanding about the disconfirmatory effects on the formation of dining satisfaction, and how satisfaction affects post-dining behavioral intentions in Malaysia coffeehouse. The main objective of this study is to study the theoretical understanding about the disconfirmatory effects on the formation of dining satisfaction in Malaysia. Besides that this paper will access the attributes which contributed to customers' satisfaction and measure the probability of return as a consequence of dining satisfaction in specialty coffeehouse. From the results of the study, we concluded that post-dining satisfaction towards the specialty coffeehouse may not directly lead to return patronage. Second, marketer should put in extra effort in narrowing the gap between pre-dining and post-dining perception because customers' expectations are not easily met. Third, the attributes that marketers can improve to narrow the gap between pre-dining and post-dining perception are those attributes under the 'a coffeehouse that...'. Finally, the conceptual model for customer satisfaction and return patronage suggested by Kivela et al (1999(1)) may not be applicable to all type of restaurant, especially the specialty coffeehouse involved in this study. Thus, other factors which may influence customers' decision to return to the restaurant should be further studied.